L'amenagement forestier au Gabon: historique, bilan, perpectives - Drouineau, S.; Nasi, Robert (Centre de Coopération Internationale en Recherche Agronomique pour le Développement, 1999)
There is growing awareness of the need to sustainably manage forests in Central Africa. This paper reviews the current state in Gabon within the national context. Forests play a very important role in Gabon in view of their extensive area as well as their contribution to the national economy. There are three main forest regions: coastal sedimentary basin, North-East, and Central Gabon. Forest utilisation is largely controlled by foreign capital and includes few tree species, mainly Okoumé (75% in 1997), with comparatively low volumes extracted per hectare. Export of Okoumé and Ozigo was until recently a monopoly of SNBG, a state company now experiencing a deep crisis. The timber market is affected by the Asian crisis repercussions. Since the 50s the government, as owner, has tried to sustainably manage the forests. Pilot management schemes were undertaken and all forest concessions are required by law to have management plans. The main problem for the government is its capacity to enforce forest management, and for the concession holders the profitability of their investments. There are internal incentives (better forecast of harvest, rationalisation of forest road network, guarantee of access to managed forests), as well as international incentives, such as pressure for ecocertification and assistance to forest management. At national level the forest law reform will make sustainable management compulsory. Such constraints and incentives are not fully identified, however there is clearly increasing involvement of logging companies: feasibility studies on management of timber concessions, forest management agreements between government and concession holders. The cost of sustainable forest management appears globally acceptable. The success of a forest management policy in Gabon will depend on the capacity of the government to incorporate management as a natural component of forest utilisation, and control implementation.